Handbook of globalisation and tourism - Timothy, Dallen J. (Cheltenham, UK Northampton, MA Edward Elgar Publishing, 2019)
"This comprehensive Handbook brings together conceptual contributions from leading international scholars concerning the reciprocal relations between globalisation and tourism. Contributors deconstruct the global forces, processes and challenges that face the tourism industry, analysing the effects of neoliberalism and multinational capitalism on global tourist activity, as well as the consequences of colonialism, terrorism, warfare, climate change, modern technological advances and the rapidly changing dynamics of global mobility. International in scope and empirically evocative, this Handbook outlines and dissects the social, cultural, economic and political effects of globalisation on tourism in the 21st century. This Handbook is critical to human geography and tourism studies scholars and researchers at all levels, particularly those interested in the relations between globalisation and tourism in an increasingly interconnected world"--
Includes bibliographical references and index.
Keywords: Globalization and tourism